L'AEROFOTOTECA NAZIONALE RACCONTA..... MULTI-TEMPORAL PHOTOINTERPRETATION - Graciotti, Roberto (GEOmedia, 2019)
Aerial photographs, if taken to allow a stereoscopic vision, can increase the physical and anthropic information of terrestrial survey acquired by means of direct field surveying. The synoptic view from above even of vast areas shows, almost immediately, the configuration of the terrain, the mutual relationships of the elements and objects present and the main forms of erosion and accumulation that characterize it. The observation of aerial photos allows investigating even inaccessible areas, characterized by steep slopes, high altitude, little or no traffic, where access is difficult, or areas where access is impossible.